2020
DOI: 10.1371/journal.pone.0233843
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of vestibulocortical interactions during standing in healthy subjects

Abstract: The vestibular system is essential to produce adequate postural responses enabling voluntary movement. However, how the vestibular system influences corticospinal output during postural tasks is still unknown. Here, we examined the modulation exerted by the vestibular system on corticospinal output during standing. Healthy subjects (n = 25) maintained quiet standing, head facing forward with eyes closed. Galvanic vestibular stimulation (GVS) was applied bipolarly and binaurally at different delays prior to tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 89 publications
(120 reference statements)
0
3
0
Order By: Relevance
“…Stochastic resonance refers to the improved ability to detect stimuli, or better output signal quality, in a nonlinear system with the addition of noise [ 19 , 20 ]. The effects of nGVS are likely the result of the fact that the vestibular afferents terminate in the vestibular nuclei, which can influence motor behavior through their connections with oculomotor circuitry and via the vestibulospinal tract [ 21 , 22 , 23 ]. Since the vestibular nuclei have dense connections with the thalamus, nGVS has the potential to affect a variety of brain regions and thus behavior [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Stochastic resonance refers to the improved ability to detect stimuli, or better output signal quality, in a nonlinear system with the addition of noise [ 19 , 20 ]. The effects of nGVS are likely the result of the fact that the vestibular afferents terminate in the vestibular nuclei, which can influence motor behavior through their connections with oculomotor circuitry and via the vestibulospinal tract [ 21 , 22 , 23 ]. Since the vestibular nuclei have dense connections with the thalamus, nGVS has the potential to affect a variety of brain regions and thus behavior [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additional maneuvers have been added to evaluate the effect of GVS on the H-reflex, for example, it was found that posture influences H-reflex amplitude facilitated by GVS ( Tanaka et al, 2021 ). The head position must also be considered while assessing H-reflex amplitude ( Okada et al, 2018 ; Nepveu et al, 2020 ). In 10 healthy subjects, Kennedy and Inglis (2002) found that H-reflex modulation by GVS showed a larger response with anodal stimulation and subjects turning to the right, and cathodal stimulation with subjects turning to the left, than any other polarity or head position combination ( Kennedy and Inglis, 2002 ).…”
Section: Introductionmentioning
confidence: 99%
“…Another study used GVS and TMS as vestibular and corticospinal input, respectively, to determine its influence at premotor (H-reflex) and motoneuron (electromyography) levels by analyzing amplitude and latency. The results suggested that modulation with GVS occurs at premotor neuron and motor neuron levels but is not influenced by cortical activity ( Nepveu et al, 2020 ). Moreover, cerebellar repetitive TMS followed by noisy GVS facilitated the H-reflex ratio excitability recorded 100 ms after a vestibulospinal function test performed with squared GVS in healthy adults.…”
Section: Introductionmentioning
confidence: 99%